"Plasma‐Click" Based Strategy for Obtaining Antibacterial Surfaces on Implants. Issue 4 (18th January 2013) - Braceras, Iñigo; Oyarbide, Joseba; Azpiroz, Patxi; Briz, Nerea; Ipiñazar, Enrique; Álvarez, Noelia; Atorrasagasti, Garbiñe; Fratila, Raluca M.; Aizpurua, Jesus M.
Abstract Biomaterials with surface antibacterial properties are promising components for medical implants that might provide an alternative to conventional systemic antibiotic treatments. Herein is reported a general method, based on plasma polymerization techniques, to promote the formation of "clickable surfaces" which can be conjugated with chemically modified antibiotics (e.g., azido‐vancomycin) under very mild conditions. The procedure is comprised of three operations: (i) surface alkylcarboxylation with acrylic acid/CO2 plasma, (ii) alkyne functionalization by condensation with propargylamine, and (iii) in situ Cu(I)‐catalyzed alkyne–azide conjugation with azidovancomycin. The antibacterial activity of the resulting functionalized surfaces has been assessed against Staphylococcus epidermidis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>